Evaluation of intranasal oxygen supplementation in mules anesthetized with the combination of ketamine, butorphanol, and guaifenesin - Módolo, T. J.C. [UNESP]; Munerato, M. S. [UNESP]; Bueno, G. M. [UNESP]; Pereira, G. T. [UNESP]; Marques, J. A. [UNESP] (FapUNIFESP (SciELO), 2017)
Hypoxemia is a major complication of field anesthesia and no studies regarding this occurrence in mules has been done. Thus, the aim of this study was to evaluate intranasal oxygen supplementation (IOS) in mules (Equus caballus x Equus asinus) anesthetized with ketamine/butorphanol/guaifenesin combination. For this, we used six male, adult mules (322±29kg) which underwent premedication (MPA) with 0.2mg/kg of midazolam intramuscularly after 15 minutes, 0.02mg/kg detomidine IV 5 minutes after, induction IV with combination of ketamine (2mg/mL), butorphanol (22.5mg/mL), and guaifenesin (50mg/mL) (K/B/G) until lateral decumbency. Maintenance was done with the same anesthetic combination. The animals were submitted twice to the protocol described above, 20 days apart, forming two groups. CG: MPA, induction (0.92±0.24mL/kg (mean±SD), and maintenance (2.2±0.2mL/kg/h) without SIO; TG: MPA, induction (0.98±0.17mL/kg), and maintenance (2.3±0.4mL/kg/h) with IOS flow 40mL/kg/h. During anesthesia arterial blood was collected every 20 minutes (T0, T20, T40, and T60) for blood gas analysis. Data analyzed by ANOVA followed by the Bonferroni test. P<0.05 was considered significant. Hypoxemia of the animals in the CG in periods (59±5; 55±5; 53±7; 49±8) with lower averages than the TG (160±4, 115±34, 92±25, 81±19) was observed, demonstrating that IOS increases PaO2 avoiding the occurrence of hypoxemia.
Keywords: Detomidine; Field anesthesia; Hypoxemia; IOS; Total intravenously anesthesia